The Juvenile Court Meets the Principle of the Offense: Legislative Changes in Juvenile Waiver Statutes - Feld, Barry C. (1987)
At its inception the juvenile court was characterized by procedural informality and individualized, offender-oriented dispositions. Subsequent to the U.S. Supreme Court's 'Gault' decision, which mandated procedural safeguards in the adjudication of delinquency, juvenile court procedures became more formal in the interest of protecting the rights of juveniles, but individualized, offender-oriented dispositions were preserved. The inability of proponents of juvenile rehabilitation to demonstrate the effectiveness of parens patriae intervention, however, has led an increasing number of States to incorporate 'just deserts' sentencing principles in their juvenile justice systems. This emphasis is evidenced in the waiver of juvenile offenders for criminal prosecution that will presumably match the disposition to the crime's severity. Proponents of just deserts in sentencing contend that there is no reliable clinical basis upon which juvenile court judges can make accurate amenability or dangerousness determinations and that the standardless discretion afforded juvenile court judges results in the inconsistent application of juvenile court waivers. This article examines legislation that has sought to standardize the waiver decision. The implications of waiver for juveniles and justice are discussed. This article supports the use of offense criteria to structure the waiver decision within statutory parameters that make juveniles less culpable than adults. The implementation of juveniles' rights to counsel is also considered. 228 footnotes